Effect Of Job Benefits, Employee Turnover, Working Environment On Employee Satisfaction: Evidence From Hospitality Industry Of Malaysia - et. al., Mohammad Salik Balwa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the study is to identify the relationship among job benefits, employee turnover, working environment and employee satisfaction in the restaurants of Malaysia specifically Kuala Lumpur. Quantitative methodology, non-probability sampling and questionnaire was used for this study to collect data. SPSS used to analyse the usable 200 responses. Findings reveal that job benefits and employee satisfaction has moderate relationship. Employee turnover and employee satisfaction, working environment have small effect. This study will help the owners, policy makers, industry players and stakeholders to formulate strategies to retain employee and develop work condition. Thus, the productivity and output of industry will improve.